Utilizing VR-BCI for motor function rehabilitation. - Thi Chau, Ma; Nguyen Minh, Kien; Vu Thanh, Long; Nguyen The, Hoang Anh; Huynh Thi Nhu, Y; Dang Huynh, Loc; Doan Van Anh, Vu; Vo Ngoc, Duy; Hoang Tien Trong, Nghia (Technology & Disability, 2025)
Brain-computer interface (BCI) is a promising interactive technology for restoring motor function in patients with motor neuron diseases. Combining virtual reality (VR) with BCI has shown better rehabilitation results, yet research and practical applications remain limited, especially in Vietnam. This research aims to introduce a comprehensive VR-BCI system to aid patients with motor function impairments in the recovering process. This approach seeks to improve neuroplasticity and recovery through immersive interactions, also advancing the development of effective rehabilitation tools, particularly in developing countries with limited access to advanced medical technologies, such as Vietnam. Using affordable Electroencephalogram (EEG) and VR devices, the system is optimized for Vietnamese healthcare standards, providing an accessible solution for home-based therapy. Key features include EEG data processing through digital signal processing techniques, custom-designed VR scenarios, and personalized exercise modules. Initial trials with five stroke patients show promising improvements in motor control, particularly in 2 patients with minimal signal interference and high engagement. Feedback from users and healthcare professionals highlights the system's usability and potential to improve motor rehabilitation outcomes.